Transformation of Terms Ḥārth in Quranic Translation: Comparing Colonial-Era and Contemporary Translations - Mukminin, Muhamad Saiful; Alfath, Muhammad Habibie; Ahmed, Aqeel (Islamic Religious Education Departement, 2026)
Differences in translations across periods often lead to variations in meaning, making terminological transformation inevitable. This study aims to analyze in depth the transformation of the term Ḥārth in two versions of the Qur'an translation, namely during the colonial period and the present day. The methodology is a qualitative approach combining descriptive, comparative, and interpretive methods. The research data are drawn from all verses containing the element Ḥārth in the Tafsir Qur'an Karim by Mahmud Yunus, as well as the official version from the Indonesian Ministry of Religious Affairs. The results show that Ḥārth has a broad meaning, encompassing farming, land, and metaphorical uses. The identified transformation patterns include shifts from place to product, from product to place, from singular to plural, and from literal to metaphorical, influenced by socio-cultural context and reading styles over time. This study recommends that academics and translation institutions pay more attention to historical-linguistic aspects to maintain the relevance and accuracy of theological messages in changing times.